Non-epithelial tumors of the nose, nasopharynx and paranasal sinuses - a clinicopathological study - Alam, ABMK; Talukder, DC; Aich, ML; Harun, MAA; Rumi, SNF; Islam, MN (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13237 J. Dhaka Med. Coll. 2012; 21(1): 41-45